Conductor-insulator quantum phase transitions - Dobrosavljevic, Vladimir; Trivedi, Nandini; Valles, James M. (Oxford : Oxford University Press, 2012)
When many particles come together how do they organise themselves? And what destroys this organisation? Combining experiments and theory, this book describes intriguing quantum phases - metals, superconductors and insulators - and transitions between them.
Description based on online resource; title from PDF title page (viewed on July 9, 2012).
Includes bibliographical references.
Keywords: Phase transformations (Statistical physics)